Uji Konfirmasi Morfin dengan Metode KLT - P. Pebe, Maria Anjela (Program Studi Akuntansi IKOPIN, 2022)
Morphine is one of the opiate analgesic drugs. Morphine has dependent properties. So it is forbidden to use without a doctor's prescription. Is an opiate compound and determines the type of opiate compound, namely morphine. In 14 reviewed journals, the results stated that the analysis of morphine in samples using the TLC method gave good and sensitive results.